2015
DOI: 10.2135/cropsci2014.07.0508
|View full text |Cite
|
Sign up to set email alerts
|

Cellular and Molecular Mechanisms for Elevated CO2–Regulation of Plant Growth and Stress Adaptation

Abstract: Increases in atmospheric CO2 concentration have exerted significant impacts on plant growth. Numerous studies have reported positive effects of elevated CO2 on plant growth and adaptation to various environmental stresses in many plant species. The mechanisms by which CO2 enrichment regulates plant growth and stress adaptation are not completely understood. There have been some recent exciting advances in elucidating the cellular, metabolic, and molecular basis for increased growth under elevated CO2. At the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
37
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 57 publications
(39 citation statements)
references
References 149 publications
(404 reference statements)
2
37
0
Order By: Relevance
“…However, the drought‐induced water deficit was less severe for plants grown at elevated CO 2 concentration, suggesting that elevated CO 2 facilitated the maintenance of leaf hydration under drought stress. Reduction in water loss by elevated CO 2 concentration has been attributed to the induction of stomatal closure and reduction in transpiration rate (Ainsworth and Rogers, 2007; Leakey et al, 2009; Yu et al, 2012a; Burgess and Huang, 2014a, 2016; Huang and Xu, 2015). Despite reductions in stomatal conductance and CO 2 influx during drought, elevated CO 2 can increase leaf‐level water use efficiency, defined as the net photosynthesis per unit transpirational water loss, compared with plants grown at ambient CO 2 through upregulation of various enzymes involved in the Calvin cycle (Huang and Xu, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the drought‐induced water deficit was less severe for plants grown at elevated CO 2 concentration, suggesting that elevated CO 2 facilitated the maintenance of leaf hydration under drought stress. Reduction in water loss by elevated CO 2 concentration has been attributed to the induction of stomatal closure and reduction in transpiration rate (Ainsworth and Rogers, 2007; Leakey et al, 2009; Yu et al, 2012a; Burgess and Huang, 2014a, 2016; Huang and Xu, 2015). Despite reductions in stomatal conductance and CO 2 influx during drought, elevated CO 2 can increase leaf‐level water use efficiency, defined as the net photosynthesis per unit transpirational water loss, compared with plants grown at ambient CO 2 through upregulation of various enzymes involved in the Calvin cycle (Huang and Xu, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Along with possible increases in drought incidence due to global climate changes, atmospheric CO 2 concentrations have been steadily increasing and are expected to double within the next 100 years (Solomon et al, 2007). Elevated atmospheric CO 2 under optimal conditions or interacting with abiotic stress has been shown to influence many aspects of plant development, and most studies have reported positive effects for mitigation of abiotic stress damages in various plant species (Ceulemans and Mousseau, 1994; Ainsworth et al, 2002; Kirkham, 2011; Huang and Xu, 2015), including perennial grasses used in turfgrass settings, such as Kentucky bluegrass ( Poa pratensis L.), tall fescue ( Festuca arundinacea Schreb. ), and creeping bentgrass ( Agrostis stolonifera L.) (Wall et al, 2001; Lin and Wang, 2002; Qaderi et al, 2006; Yu et al, 2012a, 2012b; Burgess and Huang, 2014b, 2016).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Elevated atmospheric CO 2 concentration (eCO 2 , commonly 500–800 µmol mol −1 ) can promote plant photosynthesis and productivity, and enhance plant tolerance to environmental stresses (e.g. heat or drought stress) . Hence, CO 2 enrichment is also an effective practice to increase yield that has been widely adopted in vegetable cultivation in greenhouses .…”
Section: Introductionmentioning
confidence: 99%
“…heat or drought stress). 3,4 Hence, CO 2 enrichment is also an effective practice to increase yield that has been widely adopted in vegetable cultivation in greenhouses. 1,5,6 The yield increase can result from increased plant productivity and/or greater carbon allocation to sinks (i.e.…”
Section: Introductionmentioning
confidence: 99%